Science and engineering projects using the Arduino and Raspberry Pi : explore STEM concepts with microcomputers - Bradt, Paul; Bradt, David (Apress, 2020)
Hone your understanding of science and engineering concepts with the versatile Arduino microcontroller and powerful Raspberry Pi mini-computer. The simple, straightforward, fun projects in this book use the Arduino and Raspberry Pi to build systems that explore key scientific concepts and develop engineering skills. Areas explored include force/acceleration, heat transfer, light, and astronomy. You'll work with advanced tools, such as data logging, advanced design, manufacturing, and assembly techniques that will take you beyond practical application of the projects you'll be creating. Technology is ever evolving and changing. This book goes beyond simple how-tos to teach you the concepts behind these projects and sciences. You'll gain the skills to observe and adapt to changes in technology as you work through fun and easy projects that explore fundamental concepts of engineering and science. What You'll Learn Measure the acceleration of a car you're riding in Simulate zero gravity Calculate the heat transfer in and out of your house Photography the moon and planets Who This Book Is For Hobbyists, students, and instructors interested in practical applications and methods to measure and learn about the physical world using inexpensive Maker technologies.